On the day you were born - Frasier, Debra (San Diego : Harcourt Brace, 1991)
The earth celebrates the birth of a new baby in an environmental story that includes factual information on the natural features of the planet, the sun, moon and stars, animals and people.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
5.1
5.1
3-6.
Keywords: Childbirth -- Juvenile literature; Birth; Childbirth; Earth -- Juvenile literature; Earth; Earth